Under-Vaccination in Pediatric Liver Transplant Candidates with Acute and Chronic Liver Disease—A Retrospective Observational Study of the European Reference Network TransplantChild - Tobias Laue; Zeynep Demir; Dominique Debray; Mara Cananzi; Paola Gaio; Valeria Casotti; Lorenzo D’Antiga; Vaidotas Urbonas; Ulrich Baumann (Children, 2021)
Infection is a serious concern in the short and long term after pediatric liver transplantation. Vaccination represents an easy and cheap opportunity to reduce morbidity and mortality due to vaccine-preventable infection. This retrospective, observational, multi-center study examines the immunization status in pediatric liver transplant candidates at the time of transplantation and compares it to a control group of children with acute liver disease. Findings show only 80% were vaccinated age-appropriately, defined as having received the recommended number of vaccination doses for their age prior to transplantation; for DTP-PV-Hib, less than 75% for Hepatitis B and two-thirds for pneumococcal conjugate vaccine in children with chronic liver disease. Vaccination coverage for live vaccines is better compared to the acute control group with 81% versus 62% for measles, mumps and rubella (p = 0.003) and 65% versus 55% for varicella (p = 0.171). Nevertheless, a country-specific comparison with national reference data suggests a lower vaccination coverage in children with chronic liver disease. Our study reveals an under-vaccination in this high-risk group prior to transplantation and underlines the need to improve vaccination.